Level of Peer’s Social Support to Class XI-Social Majoring Students for The 2020-2021 Academic Year - Agnes Asa; Indra Yohanes Kiling; R. Pasifikus Christa Wijaya (Universitas Nusa Cendana, 2021)
Peer group social support is a form of attention, affection and comfort that comes from important people in life, especially within the scope of friendship at school and outside school. This study aims to determine the level of peer social support in class XI IPS students in the 2020/2021 academic year at SMAN 6 Kupang City. The approach in this study is a quantitative approach. The respondents of this study were 52 high school students. Data collection techniques using the Likert scale of peer social support. Data collection techniques Chronbach alpha scale of 0.95 respondents. The results of the study found that there was peer social support for class XI IPS students at SMAN 6 Kupang City. Based on gender, it was found that female students experienced peer social support with a percentage of 55.8% higher than male students with a percentage value of 44.2%.